Biogas potential for electric power generation in Pakistan: A survey. (February 2016) - Uddin, Waqar; Khan, B.; Shaukat, Neelofar; Majid, Muhammad; Mujtaba, G.; Mehmood, Arshad; Ali, S.M.; Younas, U.; Anwar, Muhammad; Almeshal, Abdullah M.
Abstract: From last decade, Pakistan is facing the severe problems of energy deficiency. Every year Pakistan׳s government is spending more than 14.5 billion US dollars to import crude oil in order to fulfill the energy gap. Energy demand is increasing rapidly but exploration and use of renewable energy is not meeting the needs of requirements. The unavailability of power in Pakistan lasts for 14–20 h per day. In this paper, the potential of biogas is reviewed to meet the energy requirement of Pakistan. One cubic meter of biogas can generate an electrical energy of 2.5 KWh. The annual growth rate of livestock sector is 4% in Pakistan and its dung can produce 35.625 million KWh of electric energy per day. We can overcome the energy crisis by efficiently using biogas as an alternative energy source. The installation cost of biogas plant is not only economical but also beneficial in reducing respiratory and eye infections. PCRET has installed 4109 biogas plants across the country which saves average of Rs. 37.925 million per month in terms of kerosene oil, wood, liquefied petroleum gas and bio fertilizer.